Effectiveness of a behavioral medicine intervention in physical therapy on secondary psychological outcomes and health-related quality of life in exercise-based cardiac rehabilitation: a randomized, controlled trial - Sabina Borg; Birgitta Öberg; Lennart Nilsson; Joakim Alfredsson; Anne Söderlund; Maria Bäck (BMC, 2023)
Abstract Background Interventions promoting adherence to exercise-based cardiac rehabilitation (exCR) are important to achieve positive physical and psychological outcomes, but knowledge of the added value of behavioral medicine interventions for these measures is limited. The aim of the study was to investigate the added value of a behavioral medicine intervention in physical therapy (BMIP) in routine exCR on psychological outcomes and health-related quality of life (HRQoL) versus routine exCR alone (RC). Methods A total of 170 patients with coronary artery disease (136 men), mean age 62.3 ± 7.9 years, were randomized at a Swedish university hospital to a BMIP plus routine exCR or to RC for four months. The outcome assessments included HRQoL (SF-36, EQ-5D), anxiety and depression (HADS), patient enablement and self-efficacy and was performed at baseline, four and 12 months. Between-group differences were tested with an independent samples t-test and, for comparisons within groups, a paired t-test was used. An intention-to-treat and a per-protocol analysis were performed. Results No significant differences in outcomes between the groups were shown between baseline and four months or between four and 12 months. Both groups improved in most SF-36 domains, EQ-VAS and HADS anxiety at the four-month follow-up and sufficient enablement remained at the 12-months follow-up. Conclusion A BMIP added to routine exCR care had no significant effect on psychological outcomes and HRQoL compared with RC, but significant improvements in several measures were shown in both groups at the four-month follow-up. Since recruited participants showed a better psychological profile than the general coronary artery disease population, further studies on BMIP in exCR, tailored to meet individual needs in broader patient groups, are needed. Trial registration number NCT02895451, 09/09/2016, retrospectively registered.